Iron dissolution and passivation in K2CO3-KHCO3 solutions. Rotating ring disc electrode and XPS studies - Castro, Élida Beatriz (1991)
Rotating ring-disc electrode studies on the anodic dissolution and passivation of iron in potassium carbonate/bicarbonate buffers at 25°C show that in the active anodic dissolution potential range Fe(II) soluble species are generated. This reaction is favoured by the presence of bicarbonate ions in solution and it is explained through the formation of an unstable soluble complex containing Fe(II) and HCO3−ions. This suggests that the anodic layer at a certain stage of its formation contains some amount of carbonate species. XPS data of surface layers produced at different anodic potentials confirm the presence of the carbonate species in thick anodic layers grown in the prepassive potential region in still solutions, whereas the opposite result is found for the thin passive layers formed at high positive potentials.